EVALUATION ON DEFECT PRODUCTS OF SUKA SUKA CRECKER HOME INDUSTRI USING SHEWHART CONTROL DIAGRAM - Mike Oktian; Sigit Mujiharjo; Dorlan Tobing (Jurnal Agroindustri, 2014)
Suka Suka is the business of making crackers fold in Bengkulu Selatan. In the production process there is still some defective products. This study to determine the causes of defects and evaluate the number of defects which passes within control limits. The method used is a tatistical method with Shewhart charts. From the observation can be known types of defects and possible causes of the occurrence faktor namely: the product can be caused by a torn printed dough is too liquid or operator fails during printing of oil slathered fries on the table printed, perforated products can be caused by overheating or print table the use of plastic that does not mean the crude product can be caused by the materials used does not clean or dough too long in an open container or less operator oversight of dough, broken product can be caused by the drying process babangi too dry or too loudly stirring operator during the frying process, products of oil burned can be caused by used cooking too hot or too old frying operator or product development can not be caused by a lack babangi dry or kneading machines are uneven.    Keywords :